Incidence of acute radiodermatitis in women with breast cancer undergoing hypofractionated radiotherapy - Martelletti,Laura Beatriz Sousa de Jesus (2022)
ABSTRACT Objective: To estimate the incidence and degree of acute radiodermatitis at the end and after the end of treatment in women with breast cancer undergoing hypofractionated radiotherapy. Methods: Observational, prospective, and longitudinal study, conducted between March 2019 and January 2020, in a radiotherapy outpatient clinic. Results: Thirty-two women participated in the study, among whom, in the last session of hypofractionated radiotherapy, 15 (46.9%) had radiodermatitis, erythema in 13 (40.6%), and wet peeling in 2 (6.3%). In the post-treatment evaluation, 27 (84.4%) had radiodermatitis, erythema in 17 (53.1%), dry peeling in 8 (25%), and wet peeling in 2 (6.3%). Conclusion: The general incidence of radiodermatitis after hypofractionated radiotherapy in women with breast cancer was 37.5%, erythema, 12.5%, and dry peeling, 25%. The development of care protocols for the management of radiodermatitis after treatment is of paramount importance.